Intraosseous Schwannoma of the Frontal Bone: A Case Report and Review of the Literature - Chelepy W; Yousif S; Nichols PR (International Medical Case Reports Journal, 2023)
William Chelepy, Saif Yousif, Paul Robert Nichols Department of Neurosurgery, Princess Alexandra Hospital, Brisbane, Queensland, AustraliaCorrespondence: William Chelepy, Tel +614 33308553, Email william.chelepy@health.qld.gov.auAbstract: Intraosseous schwannoma is a rare diagnosis, particularly so in the skull. Accordingly, little data exists to unify common features of this disease. Here, we present the fourth known case of a primary intraosseous schwannoma of the frontal bone: a 46-year-old male with severe, progressive headache and an osteolytic frontal bone lesion. Gross total resection of the lesion was performed with excellent clinical outcome. Histological analysis confirmed the diagnosis. The limited existing literature on this topic was reviewed to identify emerging trends surrounding presenting symptoms and treatment. Early literature suggests symptoms are often nonspecific, except for lesions of the petrous apex. No cases of recurrence have been demonstrated after gross total resection, though incomplete resection has been associated with recurrence. This diagnosis appears to be becoming a more often-considered differential for osteolytic, expansile skull lesions.Keywords: schwannoma, intraosseous, frontal bone, skull